2012
DOI: 10.1097/ajp.0b013e31823d30a2
|View full text |Cite
|
Sign up to set email alerts
|

Painful Neuromas

Abstract: Neuromas develop as part of a normal reparative process following peripheral nerve injury. Painful neuromas can induce intense pain resulting in immense suffering and disability. MRI aids the diagnosis, but, ultrasound imaging allows cost effective accurate diagnosis and localization of neuromas by demonstrating their direct contiguity with the nerve of origin. Management options for painful neuromas include pharmacotherapy, prosthetic adjustments, steroid injection, chemical neurolysis, cryoablation, and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 88 publications
(98 reference statements)
1
61
0
1
Order By: Relevance
“…After the period of degeneration, neurotrophic factors produced nearby (distal nerve stump, target organs, inflammatory cells, etc.) diffuse and attract regenerated nerve fibers from all directions [43], resulting in a bulb-shaped neuroma comprised of improperly and irregularly distributed nerve fibers intermingled closely with proliferated connective tissue, which additionally disperses the regenerated nerve fibers [44], [45]. This phenomenon was also noted in the proximal stump of the no-capping group in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…After the period of degeneration, neurotrophic factors produced nearby (distal nerve stump, target organs, inflammatory cells, etc.) diffuse and attract regenerated nerve fibers from all directions [43], resulting in a bulb-shaped neuroma comprised of improperly and irregularly distributed nerve fibers intermingled closely with proliferated connective tissue, which additionally disperses the regenerated nerve fibers [44], [45]. This phenomenon was also noted in the proximal stump of the no-capping group in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…Plasticity and “windup” related to peripheral nerve scar tissue traction, compression of residual nerves, ischemia, or peripheral upregulation of ectopic ion channels contributes to unpleasant sensations that localize to the deafferented body part (31). The microenvironment around a peripheral axotomy induces biochemical changes that result in increased expression of voltage-sensitive sodium channels, decreased potassium channel expression, altered transduction molecules involved in mechanosensitivity and heat and cold sensitivity, increased concentrations of inflammatory mediators, and altered adrenoreceptor subtype expression—the end product of which are ectopic action potentials (21,29,3234).…”
Section: Discussionmentioning
confidence: 99%
“…Herskin et al [25] confirmed that tail docking does cause an increased prevalence of neuroma formation, and that the bigger the docked part of the tail is, the higher the prevalence of neuroma formation. Neuromas are known to increase the risk for spontaneous pain and hypersensitivity [26] and thus may indicate prolonged pain experience due to tail docking, as well as an increased pain perception if the tail is later on bitten.…”
Section: Reviewmentioning
confidence: 99%